The Implementation of Telemarketing Strategy on Refinancing Products in Bank Panin Dubai Syariah Malang - Aisyah, Esy Nur (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
This study aims to find out how Bank Panin Dubai Syariah Malang Branch formulates telemarketing strategies to determine which customers have the potential to refinance by looking at existing customer data. Islamic banking must have an effective, efficient, and measurable marketing strategy to dominate market segments and have appeal to consumers, and compete with other banks including conventional banks. The methodology used in this study was qualitative and used observation and interview methods to obtain data. The results showed that Telemarketing is a method of marketing over the phone to increase customers. Telemarketing in providing financing products to customers at Bank Panin Dubai Syariah is carried out with the provisions set by the Head Office of Bank Panin Dubai. With this type of Outbound Telemarketing, a long-term relationship with the consumer or customer increases value for both parties. Refinancing through Telemarketing may be binding under an oral agreement.